ANALISIS KREDIT USAHA TERHADAP PERTUMBUHAN EKONOMI ISLAM DAN KONVENSIONAL - Tarmizi Tarmizi (Universitas Teuku Umar, 2018)
Economic crisis that hit Indonesia has not ended until now has provided an overview of the need to specify an alternative economic system. A system that will facilitate economic growth but at the same time equalization. Order system that favor everyone, which is a system that provides an opportunity widest on the market mechanism, but still give a role to the government, the power of social and legal, to intervene and correction to ensure the economic power is not concentrated to a small group of businessmen, in addition to be able to do a lot of economic empowerment, as well as providing inner and outer well-being intrinsically. The system in question is the economic system of Islam. Keywords: Credit, Conventional, Islamic Economics.